2013
DOI: 10.4322/rbeb.2013.012
|View full text |Cite
|
Sign up to set email alerts
|

Influência de parâmetros da estimulação elétrica funcional na contração concêntrica do quadríceps

Abstract: Resumo Introdução: Sistemas de estimulação elétrica funcional (FES) são usados na prática clínica para o fortalecimento muscular, assim como para a recuperação e preservação funcional dos músculos enfraquecidos. Porém, uma das dificuldades encontradas na sua aplicação é a falta de padrões adequados para a realização de um movimento pré-estabelecido, uma vez que os parâmetros da estimulação (frequência, intensidade de corrente e duração do pulso) são variados heuristicamente. O presente … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…Between rPET/rGO-1.0 electrodes (ϕ 18 mm), called electrode I, and rPET/rGO-1.0 electrodes (ϕ 10 mm), called electrode II, we observed that the electrode II and Ag/AgCl electrode have linear performance at different frequencies, with different current magnitude. According to Bohórquez et al [ 48 ], the constitution of the electrode materials, the particularities of any body, as well as the diameter of the segment to be stimulated, are essential to the impedance variations of the system. In theory, the electrode size is inversely proportional to the current density, i.e., smaller electrodes cause the current to pass through a smaller area, obtaining lower impedances, thus improving the electrode-skin sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Between rPET/rGO-1.0 electrodes (ϕ 18 mm), called electrode I, and rPET/rGO-1.0 electrodes (ϕ 10 mm), called electrode II, we observed that the electrode II and Ag/AgCl electrode have linear performance at different frequencies, with different current magnitude. According to Bohórquez et al [ 48 ], the constitution of the electrode materials, the particularities of any body, as well as the diameter of the segment to be stimulated, are essential to the impedance variations of the system. In theory, the electrode size is inversely proportional to the current density, i.e., smaller electrodes cause the current to pass through a smaller area, obtaining lower impedances, thus improving the electrode-skin sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…The cathode positioning was guided by the determination of the motor point on the upper lateral surface of the quadriceps muscle. The motor area of greatest muscle contraction was used to position the cathode 20,21 . During electrostimulation, patients were supine, with their knees at 30º of flexion, being encouraged to perform isometric contractions concomitantly with the electrical stimulus 12 .…”
Section: Methodsmentioning
confidence: 99%
“…During electrostimulation, patients were supine, with their knees at 30º of flexion, being encouraged to perform isometric contractions concomitantly with the electrical stimulus 12 . All sessions lasted 30 minutes, with a frequency of 50 Hertz (Hz), pulse duration of 300 microseconds, rise time of 1 second, stimulus time (ON) of 5 seconds, descent time of 1 second and time of 10 seconds of relaxation (OFF) 12,20 . Intensity was adjusted according to the patient's tolerance, with approximately 100 contractions per session.…”
Section: Methodsmentioning
confidence: 99%
“…The electromyographic examination revealed a significant effect on the neuromuscular activation pattern due to the restoration of the strength of the muscle through neuromuscular facilitation and increasing the velocity of propagation of action potentials of motor units 17 that promote an increase in muscular action 18 and improves intermuscular and intramuscular coordination of agonists and antagonists 19,20 . The assessment of postural control represents a challenging task but has important implications to professionals from diverse areas such as neurology, physiotherapy, and orthopedics 21 .…”
Section: T Guwn Vu" "mentioning
confidence: 99%